Analisis Rasio Risk Based Capital, Rasio Likuiditas, Rasio Solvabilitas, Underwriting Ratio Pada Pt Asuransi Bintang, Tbk Pasca Ojk (Otoritas Jasa Keuangan) - Ch.Dini Ika Handayani (Jurnal Solusi, 2018)
The financial report is one of the tools that can be used to know the financial condition of the company. Financial statements present the financial position and the overview of the company’s performance in generating profits. To find out the company’s health condition can be seen from the ratio-financial ratio. On the insurance company, financial ratios that are used to assess the financial performance is the ratio of risk based capital ratios, liquidity, solvency ratio and underwriting ratio. Risk Based Capital Ratio of PT Asuransi Bintang, Tbk from year 2011 up to 2016 is always above 120 percent. This means that the financial good health condition. Ratio liquidity is at a range of 850.56% up to 1762.69%. This reflects the liquidity of the company is very good. The value of the Debt Ratio in table 3 each year are at numbers 67%. This means that 67% of total assets financed with debt. Beginnning in 2012, the value of the ratio of underwriting is always above 50%. This means that premium income obtained two times greater than the burden of underwriting .